2015
DOI: 10.2471/blt.14.142356
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis control and economic recession: longitudinal study of data from 21 European countries, 1991–2012

Abstract: ObjectiveTo investigate whether the economic recession affected the control of tuberculosis in the European Union.MethodsMultivariate regression models were used to quantify the association between gross domestic product, public health expenditure and tuberculosis case detection rates, using data from 21 European Union member states (1991–2012). The estimated changes in case detection attributable to the recession were combined with mathematical models of tuberculosis transmission, to project the potential inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 35 publications
0
31
0
1
Order By: Relevance
“…However, tuberculosis is not often transmitted from migrants to the resident population 39 and WHO’s Regional Office for Europe continues to provide support in response to the migrant and refugee crisis 40 . Possible cuts in public health spending and social protection may also permit increases in tuberculosis incidence and mortality 9 , 41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tuberculosis is not often transmitted from migrants to the resident population 39 and WHO’s Regional Office for Europe continues to provide support in response to the migrant and refugee crisis 40 . Possible cuts in public health spending and social protection may also permit increases in tuberculosis incidence and mortality 9 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…At the same time, economic crises, growing inequity, increases in the incidence of diseases that are risk factors for tuberculosis and the dissemination of drug-resistant forms of Mycobacterium tuberculosis may all be contributing to an expansion in the burden posed by tuberculosis 6 – 9 …”
Section: Introductionmentioning
confidence: 99%
“…1 Portugal is among the 10 poorest countries of the European Union, and recently underwent a deep economic recession due to the global economic crisis, which led many countries to reduce their support for TB control programmes. 2 Portugal, a country with a medium to low incidence of TB, reached an incidence of 20 per 100 000 population for the first time in 2014, and has one of the highest TB burdens in Europe. 3,4 The scientific and public health communities recognise the fact that to attain the TB targets, including its eradication, it is necessary to expand the scope of TB control beyond the usual efforts by addressing one of the drivers of the epidemic: the socio-economic determinants of health.…”
Section: O N C L U S I O Nmentioning
confidence: 99%
“…Reeves et al 35 analyzed 21 European countries in an attempt to assess the impacts of economic recession on the control of tuberculosis. The authors concluded that reductions in spending on public health services led to reduced tuberculosis case detection and increased long term risk of a resurgence in the disease.…”
Section: Infectious Diseasesmentioning
confidence: 99%